Our anesthetic results in preterm infants undergoing patent ductus arteriosus ligation [Patent Duktus Arteriosus Ligasyonu Yapilan Prematüre Infantlarda Anestezi Sonuçlarimiz] - (:unkn) unknown (Turkish Anaesthesiology and Intensive Care Society, 2016)
Objective: In preterm infants with patent ductus arteriosus, due to low birth weight, interventional difficulties and ventilation problems caused by bronchopulmonary dysplasia are commonly observed. In this study, ice analysed the anaesthetic approach, hemodynamics and surgical complications in these high risk patients. Material and Methods: After the approval of the scientific committee and the informed consent of the patients were obtained, 39 preterm patients scheduled for PDA ligation in our paediatric heart surgery clinic ivere enrolled in the stiuly. Data related to birth weeks, birth weight, additional cardiac pathology and the necrotising enterocolitis were recorded. Hemodynamic data such as blood pressure, heart rate, SaO and NIRS were monitored and complications such as hypotension, bradycardia and bleeding were determined. Results: Mean gestational age al birth (28.49±2.72 weeks), mean age (24.02+6.35 days), and birth weights (924.43+30.70 g) were recorded for weight. During the surgery, transient hypotension due to bradycardia was observed in 25.6% of the cases. Discussion find Conclusion: In preterm infants undergoing PDA ligation, risk of transient hypotension, bradycardia and low oxygen saturation is detected during anaesthesia. We concluded that close observation of hemodynamics during anaesthetic management in these patients with low birth weight who may have congestive heart failure carries utmost importance.
Keywords: Anaesthesia; Patent ductus arteriosus ligation; Preterm infant